Cytokine mRNA repertoire of peripheral blood mononuclear cells in Takayasu's arteritis - TRIPATHY, N KUMAR (Blackwell Science Inc, 2004)
We have investigated constitutive and phytohaemagglutinin (PHA) + phorbol 12-myristate 13-acetate (PMA)-induced gene expression of tumour necrosis factor (TNF)-α, interferon (IFN)-γ, interleukin (IL)-2, IL-3, IL-4, IL-10, IL-12 and granulocyte macrophage colony-stimulating factor (GM-CSF) in peripheral blood mononuclear cells (PBMCs) of 10 patients with Takayasu's arteritis (TA) and 10 healthy controls by semiquantitative reverse transcriptase polymerase chain reaction (RT-PCR). The constitutive mRNA expression of TNF-α (69·0 ± 4·0% versus 27·5 ± 18·0%; P = 0·001) and IL-4 (60·0 ± 10·0% versus 0%; P = 0·001) was significantly higher in patients than controls; that of IL-3 was comparable in both groups (38·0 ± 6·0% versus 32·0 ± 5·0%; P = 0·651) while no constitutive mRNA expression was observed for the other cytokines studied. The stimulated PBMCs of patients, as compared with the controls, had higher mRNA gene expression of TNF-α (127·0 ± 16·0% versus 54·0 ± 6·0%; P = 0·001), IFN-γ (93·0 ± 13·0% versus 57·0 ± 5·0%; P = 0·032), IL-2 (109·0 ± 13·0% versus 68·0 ± 6·0%; P = 0·015), IL-3 (60·0 ± 8·0% versus 21·2 ± 3·0%; P = 0·045) and IL-4 (68·0 ± 7·0% versus 27·0 ± 7·2%; P = 0·01) The mRNA expression of IL-10 was lower in patients than controls (35·0 ± 8·0% versus 75·0 ± 12·0%; P = 0·022). The GM-CSF mRNA was similar (102·0 ± 6·0% versus 89·0 ± 5·0%; P = 0·475) in both groups. Stimulation of cells with PHA + PMA showed no IL-12 expression but stimulation with lipopolysaccharide induced higher IL-12 mRNA in patients than controls (83·0 ± 14·0% versus 33·0 ± 4·0%; P = 0·005). Our data suggest that an inflammatory cytokine signature exists in TA with a key role for TNF-α, IL-4, IL-10 and IL-12 in different pathological processes of the disease.